2005
DOI: 10.1158/1078-0432.ccr-05-0141
|View full text |Cite
|
Sign up to set email alerts
|

High Thymidylate Synthase Expression in Colorectal Cancer with Microsatellite Instability: Implications for Chemotherapeutic Strategies

Abstract: Colon cancers displaying microsatellite instability (MSI) are clinically less aggressive. Based on in vitro studies and recent clinical data, cancers displaying MSI do not respond to 5-fluorouracil (5-FU). The reasons why MSI tumors are clinically less aggressive and do not respond to 5-FUb ased therapies have not been fully elucidated. Purpose: We investigated biomolecular markers in an attempt to explain the different clinical behavior and chemotherapeutic responses of MSI and non-MSI colon cancers. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
38
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 59 publications
10
38
1
1
Order By: Relevance
“…We observed an expression of p53 in 63% of the colorectal carcinomas which is in line with previous studies, where a range of 40 to 81% p53 positivity was found (10)(11)(12)(13). This wide range depends on different techniques used in these studies, such as different antibodies, scoring systems, cutoff-values and study populations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed an expression of p53 in 63% of the colorectal carcinomas which is in line with previous studies, where a range of 40 to 81% p53 positivity was found (10)(11)(12)(13). This wide range depends on different techniques used in these studies, such as different antibodies, scoring systems, cutoff-values and study populations.…”
Section: Discussionsupporting
confidence: 91%
“…Further, we found a significant association of p21-negative carcinomas and rectal localization. Ricciardiello et al (10) reported an enhanced p21 expression in the right colon. Apart from these studies, data on p21 and its relationship to clinical and pathological findings are rare.…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, our study shows, for the first time the relationship between these two key molecules in a group of patients with locally advanced or metastatic CRC receiving similar treatment. Other studies have only hypothesized their relationship with treatment, whereas with the clinical data available in this study we have been able to assess this relationship [8]. In the present study, we calculated a variety of indices to measure this TS-MMR co-expression, and these were related to different clinical variables, response to treatment and tested as predictors of disease outcome (DSF, DSS and survival with metastases).…”
Section: Discussionmentioning
confidence: 94%
“…This is the first study to establish such a direct relationship between hMLH1 and TS. Previously, Ricciardiello et al reported an inverse correlation between hMLH1 and TS [8], whereas the other two published studies could not establish any relation between MMR and TS [6,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation